2010
DOI: 10.1016/j.jcmg.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Heterogeneity of Vasa Vasorum Neovascularization in Human Coronary Atherosclerosis

Abstract: Objectives To investigate the role of coronary vasa vasorum (VV) neovascularization in the progression and complications of human coronary atherosclerotic plaques. Background Accumulating evidence supports an important role of VV neovascularization in atherogenesis and lesion location determination in coronary artery disease. VV neovascularization can lead to intraplaque hemorrhage, which has been identified as a promoter of plaque progression and complications like plaque rupture. We hypothesized that disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 29 publications
6
48
0
3
Order By: Relevance
“…The increased vascularization of the vessel, as shown in our results, is associated with the formation of atherosclerotic plaques and calcified formations in the vessel walls (Gössl et al, 2010;Sano et al, 2014). Higher concentrations of calcified aggregates lead to more marked collagen remodeling as we indeed found.…”
Section: Discussionsupporting
confidence: 86%
“…The increased vascularization of the vessel, as shown in our results, is associated with the formation of atherosclerotic plaques and calcified formations in the vessel walls (Gössl et al, 2010;Sano et al, 2014). Higher concentrations of calcified aggregates lead to more marked collagen remodeling as we indeed found.…”
Section: Discussionsupporting
confidence: 86%
“…The plaque microenvironment also contains high levels of eNOS and TNF-a. As a result, intra-plaque hemorrhage can occur ( particularly in noncalcified plaques, which have the highest vessel density and are more prone to rupture), accelerating plaque progression and rupture, and leading to myocardial infarction (Gossl et al 2010).…”
Section: Vascular Normalizationmentioning
confidence: 99%
“…Error bars represent S.E. TNF-␣ in atherosclerotic plaques is related to plaque remodeling and facilitates plaque rupture and thrombus formation (60,61). In our study, we found that the levels of TNF-␣ were significantly higher in the patients with NSTACS, suggesting abnormal immune activation in the NSTACS patients.…”
Section: Treg Cells Rte-treg Cellsmentioning
confidence: 99%